1985
DOI: 10.1177/019459988509300114
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status‐a Prognostic Indicator in Head and Neck Cancer

Abstract: A prospective study into the nutritional status of 114 patients with untreated primary squamous cell carcinoma of the head and neck was undertaken to assess its possible prognostic value for survival. Nutritional status was evaluated by anthropometry, creatinine height index estimation, serum albumin and transferrin assays, and nitrogen balance studies. Weight change and other anthropometric indices found to be the most reliable nutritional parameters were averaged to derive a clinically useful, general nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 20 publications
1
96
1
1
Order By: Relevance
“…Critical weight loss (CWL), defined as the involuntary weight loss of ≥5% in 1 month or ≥10% in 6 months, is a common phenomenon in head and neck cancer patients because it is present in about 30% to 55% of these patients [5,17,19,28]. CWL is clinically of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Critical weight loss (CWL), defined as the involuntary weight loss of ≥5% in 1 month or ≥10% in 6 months, is a common phenomenon in head and neck cancer patients because it is present in about 30% to 55% of these patients [5,17,19,28]. CWL is clinically of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…31 Liu S et al also demonstrated that pretreatment serum albumin levels are independent indicator of prognosis for patients with oral cavity cancer. 34 A prospective cohort study of 170 patients with advanced cancer, where lung (34%), liver (14%), and lower gastrointestinal tract (14%) malignancies accounted for almost two thirds of the primary cancers, enrolled into the palliative care unit of a regional hospital in Hong Kong demonstrated that serum albumin is an independent predictor of survival.…”
Section: Discussionmentioning
confidence: 98%
“…A vast majority (>70%) of more than one billion population of India lives in rural areas, which have inadequate access to trained providers and limited health services. As a result, most of the cases are diagnosed at later stages which result in low treatment outcomes and poor 5-year survival rate of approximately 37% (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). 2 Various clinical, biochemical, and histological prognostic factors have been identified in the literature, some generic to all cancers and some specific for oral cavity cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional status has long been recognised as the second most important factor in predicting long-term prognosis in HNC (Brookes, 1985). The consequences of malnutrition in HNC patients have been widely studied and include:…”
Section: Consequences Of Malnutritionmentioning
confidence: 99%